PENYULUHAN KEPADA ANAK-ANAK DI YAYASAN JABAR HIKMAH MUTTAQIEN - PONDOK YATIM & DHUAFA TENTANG DAMPAK PENCURIAN DAN BULLYING SERTA UPAYA PENCEGAHANNYA - Saputro, Haris Djoko; Arimbi, Diah; Dwiprigitaningtias, Indah; Andayani, Lily; Ikrardini, Zulfika; Ardan, R Ardini; Amanita, Aliesa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The outreach program to children in orphanages regarding the impact of theft and bullying, as well as preventive measures, is an important effort to raise awareness and provide better understanding to children who are vulnerable to such actions. The aim of this study is to evaluate the effectiveness of the outreach in reducing the risk of theft and bullying in orphanage environments. The method used is a descriptive approach with a qualitative design through interviews, observations, and distributing questionnaires to the children and caregivers in the orphanage. The outreach was conducted through interactive sessions with materials on the negative impacts of theft and bullying, as well as preventive strategies, including the importance of communication, empathy, and social skills. The results of the study show that after the outreach, children in the orphanage demonstrated a better understanding of the importance of protecting themselves from bullying and theft, and they exhibited higher awareness to avoid and report such incidents. This outreach program has a positive impact in creating a safer and more respectful environment in the orphanage